Expedition of thirst : exploring breweries, wineries, and distilleries across the heart of Kansas and Missouri - Dulin, Pete (University Press of Kansas, 2017)
"Set out with a true aficionado and affable guide to sample a dizzying array of beverages made in America's heartland. Expedition of Thirst maps routes that crisscross eastern Kansas and western Missouri, with stops at some 150 breweries, wineries, and distilleries along the way. Pete Dulin, a seasoned writer on the subject, explains how and why these businesses produce beer, wine, and spirits tied to regional terroir and represent the flavors of the Midwest from the Flint Hills to the Ozarks. More than a travel guide, his book is a cultural journal exploring the people, places, and craft that make each destination distinct and noteworthy. Dulin shares the stories of many of these brewers, winemakers, and distillers in their own words. Expedition of Thirst captures the character of the small business owners and makers and offers insight about their craft. For good measure, Dulin delves into the history, culture, and geography that have shaped these producers and their practices, from the impact of Prohibition to the early influence of immigrant winemakers and brewers, regional agriculture, and politics. As informative as it is engaging--even intoxicating--his Expedition is sure to work up readers' thirst to travel and discover firsthand the singular regional pleasures so richly described in these pages"--Provided by publisher